RESHAPING THE EFL CURRICULUM IN ALBANIA – MAIN FACTORS COMING FROM THE HIGH SCHOOLS OF ELBASAN - Papajani, Josilda (European Scientific Journal, ESJ, 2015)
The process of changes in the Albanian Education System has touched even the English Language Curriculum. There are a number of factors which seem to be main ones in reshaping the curriculum, by giving a great emphasis to the way things are perceived from different points of view at the same situation. Teachers, institutions, learners can influence the EFL reshaped curriculum adaptation in the High Schools of Elbasan. This paper highlights the complex process of the implementation of ELT curriculum innovations, in Albania, by taking examles as well as even from other countries undergoing the same process. It also confirms that teachers are not simply implementers of policies that are handed down to them, but they interpret, modify, alter, and implement these policies according to their beliefs and the context where these policies are being implemented. In addition, this paper, illustrates a number of factors which influence how teachers implement and make sense of ELT curriculum innovations. It will be provided significant implications and useful messages for curriculum developers, teachers’ education programs, and educational policy makers.